Correlation between resilience and social support and anxiety in obstetric nurses - Liu Xiao-Xi; Liu Wei-Hua; Ping Ma; Li Cheng-Yao; Liu Xiao-Ying; Song Ping (Sciendo, 2018)
The aim of this study was to explore the correlation between psychological resilience and social support and anxiety in obstetric nurses and to provide theoretical basis for improving the mental health of obstetric nurses.